SECULAR TRENDS OF BODY MASS INDEX AND BLOOD PRESSURE DURING 1977–2020; NATIONWIDE REGISTRY OF 2.8 MILLION ADOLESCENTS. (June 2022) - Fishman, Boris; Zloof, Yair; Orr, Omri; Tsur, Avishai M; Furer, Ariel; Omer, Ma'Ayan; Chodick, Gabriel; Leiba, Adi; Derazne, Estela; Tzur, Dorit; Afek, Arnon; Grossman, Ehud; et al.
Abstract : Objective: Adolescence elevated blood pressure is an emerging public health issue with growing evidence of its future deleterious cardiovascular and renal effects. Most data regarding systolic (SBP) and diastolic blood pressure (DBP) trajectories are based on surveys of selected adolescent populations within short periods of time. Our objective was to describe the secular trends of blood pressure and body mass index (BMI) throughout the years 1977-2020. Design and method: This nationwide population-based study comprised of 2, 785, 515 Israeli male and female (41.6%) adolescents (mean age 17.4 years) whose weight, height and blood pressure were routinely measured as part of comprehensive medical assessment prior to compulsory military service. Linear regression models were applied to calculate the P for trend along the study period separately for males and females. Predicted SBP and DBP adjusted for BMI, were calculated using the Analysis of Covariance. Results: Throughout study period, the mean BMI increased in males by 2.1 and 1.6 kg/m2 in females (P for trend < 0.001 in both sexes). The mean DBP decreased by 3.6 and 2.9 mmHg among males and females, respectively. (P < 0.001 in both sexes). While the mean SBP blood increased by 1.6 mmHg among males and decreased by 1.9 mmHg among females. These trends were consistent in models assessing BMI adjusted SBP and DBP. The trend were consistent in sub analyses stratifying the population by immigration status and by health status (existence of additional significant comorbidities). Conclusions: DBP among adolescents decreased over the the last 44 years, despite the significant increase in BMI and obesity prevalence in both sexes. Meanwhile, SBP increased slightly in males and decreased in females.